Impact of Tc-GSA SPECT Image-Guided Inverse Planning on Dose-Function Histogram Parameters for Stereotactic Body Radiation Therapy Planning for Patients With Hepatocellular Carcinoma: A Dosimetric Comparison Study - Ryo Toya; Tetsuo Saito; Yudai Kai; Shinya Shiraishi; Tomohiko Matsuyama; Takahiro Watakabe; Fumi Sakamoto; Noriko Tsuda; Yoshinobu Shimohigashi; Yasuyuki Yamashita; Natsuo Oya (SAGE Publishing, 2019)
Purpose: To evaluate the impact of 99m Tc-labeled diethylene triamine pentaacetate-galactosyl human serum albumin ( 99m Tc-GSA) single-photon emission computed tomography (SPECT) image-guided inverse planning on the dose-function histogram (DFH) parameters for stereotactic body radiation therapy planning in patients with hepatocellular carcinoma (HCC). Methods: Eleven patients were enrolled in this study. The functional liver structure (FLS) was derived from SPECT thresholds of 60% to 80% of the maximum pixel value. Two treatment plans optimized without FLS (plan C) and with FLS (plan F) were designed for 50 Gy to the planning target volume (PTV). The DFH parameters were calculated as follows: Fx = (sum of the counts within the liver volume receiving a dose > x Gy/sum of the counts within the whole liver volume) × 100. Other parameters for the PTV included D 95 , mean dose, conformity index (CI), and homogeneity index (HI). Results: Compared with plan C, plan F significantly reduced DFH parameters of F 5 to F 40 ( P < .05). There were no significant differences in the parameters of the PTV of D 95 , mean dose, CI, and HI and organs at risks (stomach, duodenum, spinal cord, and kidneys) between plans C and F. Conclusion: DFH analyses revealed that 99m Tc-GSA SPECT image-guided inverse planning provided dosimetric benefits related to sparing of liver function and may reduce hepatic toxicities.